2018
DOI: 10.1096/fj.201701148rr
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine attenuates the bone erosion in collagen‐induced arthritis rats by inhibiting osteoclastogenesis via spleen tyrosine kinase

Abstract: Tetrandrine, a bisbenzylisoquinoline alkaloid, was previously demonstrated to attenuate inflammation and cartilage destruction in the ankles of mice with collagen-induced arthritis (CIA). Here, we explored the underlying mechanism by which tetrandrine prevented arthritis-induced bone erosion by focusing on the differentiation and function of osteoclasts. We found that daily administration of tetrandrine (30 mg/kg) markedly reduced the bone damage and decreased the number of osteoclasts in CIA rats. In vitro, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…In addition, bone histomorphometry results revealed that the protective effects of fanchinoline is through inhibiting the osteoclasts activity by the relative parameter such as osteoclast number/ bone surface (N.Oc/BS) and osteoclast surface/ bone surface (Oc.S/BS). Our results are in line with recent findings showing an inhibitory effect of tetrandrine on bone loss (8,33), and also provide new mechanistic insights of fangchinoline. In conclusion, fangchinoline attenuated osteoclast formation, function and ameliorated OVX-induced osteoporosis in mice mainly through suppressing RANKL signalling pathways and osteoclast marker genes expression.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, bone histomorphometry results revealed that the protective effects of fanchinoline is through inhibiting the osteoclasts activity by the relative parameter such as osteoclast number/ bone surface (N.Oc/BS) and osteoclast surface/ bone surface (Oc.S/BS). Our results are in line with recent findings showing an inhibitory effect of tetrandrine on bone loss (8,33), and also provide new mechanistic insights of fangchinoline. In conclusion, fangchinoline attenuated osteoclast formation, function and ameliorated OVX-induced osteoporosis in mice mainly through suppressing RANKL signalling pathways and osteoclast marker genes expression.…”
Section: Discussionsupporting
confidence: 92%
“…These two recent works suggest that CEP might be useful to prevent osteoporosis. Tetrandrine was also shown to attenuate bone erosion in a model of collagen-induced arthritis (Jia et al, 2018).…”
Section: Inhibition Of Bone Resorptionmentioning
confidence: 98%
“…Accumulative evidence obtained from clinical and animal trials indicates that tetrandrine is relatively safer, and has been used to treat rheumatalgia and arthralgia in China for decades 9 . Our previous studies showed that tetrandrine could inhibit RANKL-induced osteoclastogenesis via enhancing the ubiquitylation and degradation of Syk, and attenuate the bone destruction in collagen-induced arthritis (CIA) rats 10 . Furthermore, tetrandrine was found to be a potential ligand of AhR, which could activate AhR and increase the expression of the downstream target gene CYP1A1 in murine T cells 9 .…”
Section: Introductionmentioning
confidence: 99%